Are empowered women more resilient to agricultural shocks? Evidence from women smallholder farmers in Uganda - Sanya, Losira Nasirumbi; Muhanguzi, Florence Kyoheirwe; Kavuma, Susan Namirembe; Boonabaana, Brenda; Kyomuhendo, Grace Bantebya; Ludgate, Nargiza; Meinzen-Dick, Laura; Lubyayi, Lawrence (Makerere University, 2023)
This paper draws implications for understanding the link between empowerment and resilience among rural and smallholder agricultural communities in developing contexts. While existing evidence shows that women’s empowerment promotes their individual and household well-being, women smallholder farmers continue to exhibit limited capacity to cope with climate change– induced agricultural shocks. This is exacerbated by the existing social systems and structures which hinder women’s resilience and empowerment. Using a mixedmethods approach involving the project-level Women’s Empowerment in Agricultural Index (pro-WEAI) tool and an add-on module on resilience, our research explored the relationship between women’s empowerment and resilience. The findings indicate that women in the target districts are exposed to multiple agricultural shocks and stressors. Our findings further show that women’s empowerment is linked to social and gender norms associated with women’s identity which also limit their coping ability to agricultural shocks. Women’s empowerment is associated with higher ability to recover, better access to financial services, and asset and social network indices. We conclude that women’s empowerment has strong potential to enhance resilience capacity to agricultural shocks among women smallholder farmers. This makes it imperative to address the underlying factors (including social and gender norms) that hinder women’s empowerment as a key strategy to enhancing women smallholder farmers’ resilience to agricultural shocks in Uganda. Additionally, interventions targeting climate change–induced agricultural shocks need to apply gender-transformative approaches to challenge the effect of social systems and structures on enhancing women’s empowerment and strengthening their resilience capacity.